Azide- and Alkyne-Functionalised α- and β3-Amino Acids - Sminia, Tjerk Jacco; Pedersen, Daniel Sejer (Synlett, 2012)
The synthesis and full characterisation of bifunctional β3-amino acids that have side chains functionalised with terminal azides (S)-4 and (R)-4 or acetylenes 5 and 6 is reported for the first time. The building blocks incorporate a turn-inducing β3-segment and a side chain that can be functionalised further, for example, through copper-catalysed Huisgen cycloaddition. Moreover, the corresponding α-amino acids 1 and 3 have been synthesised and characterised. All amino acid building blocks were of high optical purity as demonstrated by derivatisation and subsequent NMR analysis.
Keywords: alkynes; azides; amino acids; diazotransfer; Arndt–Eistert homologation; peptidomimetics